Konstrukcje nadziei w utopiach Roberta Owena, Charlesa Fouriera i Flory Tristan - Szumlewicz, Katarzyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2016)
In my essay „Constructions of Hope in Utopias of Robert Owen, Charles Fourier and Flora Tristan”, partly based on my monography „Emancipation through Pedagogy, or Education of Liberty, Equality and Happiness”, I examine ideas of so called utopian socialists. Are these ideas really utopian? Which was social context of their emerging? In what way utopian socialists planned to change the society and what was the role of education in this process? My thesis is that ideas of Owen, Fourier and Tristan weren't in fact more utopian (in negative sense of the word) than most Enlightenment conceptions of rational social order, for example Kantian state of goals or Rousseau's social contract. Utopian socialists were brilliant and perceptive critics of early capitalism. In their approach to sexuality and emancipation of women they were ahead of their time, much more progressive than, for example, later liberal feminist John Stuart Mill. In the area of social pedagogy they offered more appropriate solutions and more complex vision than Marx and Engels, who considered education as side issue, less important than social revolution. The irony is that these were marxists who named theories of Owen, Fourier and Tristan „utopias”...
Keywords: utopia; socialism; feminism; freedom; equality; work; exploitation; sexual liberation; emancipation